resido: an R package for exploring amino acid residue composition of peptide and protein sequences - Stonoha-Arther, Christina; Panke-Buisse, Kevin (Frontiers in Horticulture, 2025)
Amino acid composition may be used in synthetic biology for fine-tuning amino acid content of plants to improve human or animal diets. One barrier to plant-based diet adoption is insufficiency of key amino acids such as methionine and lysine. Legumes, for example, are a good source of dietary protein, but lack sufficient amounts of these essential amino acids. Despite the potential utility of exploring amino acid content in proteomes or subsets of sequences, purpose-built bioinformatic tools are largely lacking. Here, we present an R package, resido, that facilitates the characterization and discovery of proteins based on amino acid content. We used resido to investigate the sulfur-containing amino acids of white lupin (Lupinus albus L.). White lupin has the potential to be a valuable component of plant-based diets, although there are some drawbacks, one being the lack of sulfur-containing amino acids in the seeds. Using resido, we identified several protein sequences that had a high percentage of sulfur amino acids; one collagen-like protein was 25% methionine. Overall, resido is a straightforward bioinformatic tool that leverages the ubiquity of R to analyze amino acid content of user-supplied peptide sequences and may be useful to efforts modulating overall amino acid content of crops for refining nutrition in animal or human diets.